Factors that enable small enterprises to obtain debt financing from a South African financial institution - Sibisi, Nokuthula Jennifer (My University, 2018)
1.1.1 Purpose The purpose of this research is to ascertain and evaluate the factors that enable small enterprises to obtain debt financing from Standard Bank of South Africa. 1.1.2 Design/methodology/approach Archival data from a stratified random sample of 200 small enterprise business loan applications will be used to conduct the research. Descriptive methods and a statistical software package will be used to analyse the data and interpret the findings. This will be supplemented by a questionnaire survey of 15 small business relationship managers, who will be chosen via a stratified convenient method. 1.1.3 Findings The findings of the research will add to the body of knowledge about factors that enable small enterprises to obtain debt financing from Standard Bank of South Africa. The findings will be further used to help develop a theory to guide small enterprises to increase their access to debt financing by increasing their application success rates. 1.1.4 Research limitations/implications The data is readily available, the sample size is relatively small (200) and the statistical analysis required to ascertain and evaluate the factors is relatively straightforward, hence there are no limitations that are anticipated to significantly prevent the research from achieving its stated objectives. 1.1.5 Practical implication The research will add to the body of knowledge about how to increase small enterprise access to debt financing by South African financial institutions, and by extension help expand the economy by contributing to the dynamism of the small enterprise sector, in South Africa. 1.1.6 Originality/value The results from this study will create an increased understanding of the factors that enable small enterprises to obtain debt financing from Standard Bank of South Africa. Previous studies of a similar nature have not been specific to a single major financial institution in South Africa. The level of data access to a single financial institutions small business debt finance application data for research purposes is unprecedented.
MBA
Keywords: Microfinance -- South Africa. Small business -- South Africa -- Finance.